Defense strategies and associated phytohormonal regulation in Brassica plants in response to chewing and sap-sucking insects - Ali, Jamin; Tonğa, Adil; Islam, Tarikul; Mir, Sajad; Mukarram, Mohammad; Konôpková, Alena Sliacka; Chen, Rizhao (Frontiers in Plant Science, 2024)
Plants have evolved distinct defense strategies in response to a diverse range of chewing and sucking insect herbivory. While chewing insect herbivores, exemplified by caterpillars and beetles, cause visible tissue damage and induce jasmonic acid (JA)-mediated defense responses, sucking insects, such as aphids and whiteflies, delicately tap into the phloem sap and elicit salicylic acid (SA)-mediated defense responses. This review aims to highlight the specificity of defense strategies in Brassica plants and associated underlying molecular mechanisms when challenged by herbivorous insects from different feeding guilds (i.e., chewing and sucking insects). To establish such an understanding in Brassica plants, the typical defense responses were categorized into physical, chemical, and metabolic adjustments. Further, the impact of contrasting feeding patterns on Brassica is discussed in context to unique biochemical and molecular modus operandi that governs the resistance against chewing and sucking insect pests. Grasping these interactions is crucial to developing innovative and targeted pest management approaches to ensure ecosystem sustainability and Brassica productivity.